2014
DOI: 10.2175/106143013x13736496908591
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal from Wastewater by an Aerated Subsurface‐Flow Constructed Wetland in Cold Climates

Abstract: The objective of this study was to assess the role of cyclic aeration, vegetation, and temperature on nitrogen removal by subsurface‐flow engineered wetlands. Aeration was shown to enhance total nitrogen and ammonia removal and to enhance removal of carbonaceous biochemical oxygen demand, chemical oxygen demand, and phosphorus. Effluent ammonia and total nitrogen concentrations were significantly lower in aerated wetland cells when compared with unaerated cells. There was no significant difference in nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…1 SAGBs can be continuously aerated to maximize treatment of carbonaceous biological oxygen demand (cBOD) and total Kjeldahl nitrogen (TKN) with greater than 95% cBOD and 90% and TKN removal. 7 A planted, intermittently aerated vertical ow SAGB removed 54-78% of NH 4 + and 29-57% of TN as a function of hydraulic loading. 3 A similar system with continuous aeration removed 97%, 99% and 29% chemical oxygen demand (COD), NH 4 + and TN, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 SAGBs can be continuously aerated to maximize treatment of carbonaceous biological oxygen demand (cBOD) and total Kjeldahl nitrogen (TKN) with greater than 95% cBOD and 90% and TKN removal. 7 A planted, intermittently aerated vertical ow SAGB removed 54-78% of NH 4 + and 29-57% of TN as a function of hydraulic loading. 3 A similar system with continuous aeration removed 97%, 99% and 29% chemical oxygen demand (COD), NH 4 + and TN, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that sufficient oxygen supply in the soil lter enhances the removal of COD, ammonia and total nitrogen and that other factors like vegetation or temperature variations between 2 C and 20 C had only little effect on removal rates. 27…”
Section: Resultsmentioning
confidence: 99%
“…The first bench-scale research on the topic was published by Lockhart [48] and the first peer-reviewed journal article on full-scale aerated wetland application was published by Wallace and Kadlec [5]. The earliest full-scale and outdoor pilot-scale aerated treatment wetland systems received continuous (24 h/d) aeration [3,19,20,26,[49][50][51]. Many bench-scale and pilot-scale research studies have investigated the use of intermittent aeration [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Research Trendsmentioning
confidence: 99%